Allergic contact eczema - selected literature from 2018/2019 - Werfel, T.; Uter, Wolfgang (Allergologie, 2020)
Allergic contact eczema is a very important differential diagnosis of eczematous diseases that frequently occur in clinical practice. Quite frequently, contact allergy is only discovered after a meticulous, targeted diagnostic workup, which in individual cases requires a high level of medical expertise. Due to the variety and the frequently changing presence of chemicals that can trigger allergic contact eczema and due to the variability of clinical manifestations of the disease, continuing medical education of allergists and dermatologists in this specialty is of great relevance. This review paper summarizes and comments on selected publications from the years 2018 - 2019 that the authors believe could be of particular clinical interest. In addition to the updated guideline on patch testing published in 2019, highlights from studies on contact allergens from the standard series and from special series for patch testing, on contact allergies with special localizations and clinical manifestations as well as aspects of occupational dermatology are presented. This series of publications will be continued next year with literature highlights from 2019 to 2020.
CRIS-Team WoS Importer:2021-01-08